Modelling silicon supply during the Last Interglacial (MIS 5e) at Lake Baikal - Panizzo, V.N.; Swann, G.E.A.; Mackay, A.W.; Pashley, V.; Horstwood, M.S.A. (Elsevier, 2018)
Limnological reconstructions of primary productivity have demonstrated its response over Quaternary timescales to drivers such as climate change, landscape evolution and lake ontogeny. In particular, sediments from Lake Baikal, Siberia, provide a valuable uninterrupted and continuous sequence of biogenic silica (BSi) records, which document orbital and sub-orbital frequencies of regional climate change. We here extend these records via the application of stable isotope analysis of silica in diatom opal (δ30Sidiatom) from sediments covering the Last Interglacial cycle (Marine Isotope Stage [MIS] 5e; c. 130 to 115 ka BP) as a means to test the hypothesis that it was more productive than the Holocene. δ30Sidiatom data for the Last Interglacial range between +1.29 to +1.78‰, with highest values between c. 127 to 124 ka BP (+1.57 to +1.78‰). Results show that diatom dissolved silicon (DSi) utilisation, was significantly higher (p=0.001) during MIS 5e than the current interglacial, which reflects increased diatom productivity over this time (concomitant with high diatom biovolume accumulation rates [BVAR] and warmer pollen-inferred vegetation reconstructions). Diatom BVAR are used, in tandem with δ30Sidiatom data, to model DSi supply to Lake Baikal surface waters, which shows that highest delivery was between c. 123 to 120 ka BP (reaching peak supply at c. 120 ka BP). When constrained by sedimentary mineralogical archives of catchment weathering indices (e.g. the Hydrolysis Index), data highlight the small degree of weathering intensity and therefore representation that catchment-weathering DSi sources had, over the duration of MIS 5e. Changes to DSi supply are therefore attributed to variations in within-lake conditions (e.g. turbulent mixing) over the period, where periods of both high productivity and modelled-DSi supply (e.g. strong convective mixing) account for the decreasing trend in δ30Sidiatom compositions (after c. 124 ka BP).